A public health call for action to address liver cancer and hepatitis in northern Ghana - Chloe Tuck; Abdul Rashid Timtoni Iddrisu; Salimatu Asam Moro; Robert Akparibo; Richmond Aryeetey; Laura Gray; Richard Cooper (Communications Medicine)
Lack of access to diagnosis and treatment of hepatitis is unethical, resulting in avoidable liver cancer cases. Drawing on existing evidence and current research in Ghana, we identify a number of ways to address hepatitis and liver cancer in Ghana.